Analysis of blood liquor model via nonlocal and singular constant proportional Caputo hybrid differential operator. (20th January 2021) - Siddique, Imran; Akgül, Ali
Abstract : In this study, a physical scheme called the blood liquor absorption model has been examined in its fractional (non‐integer) edict form. The constant proportional Caputo (CPC) hybrid fractional operator with singular and nonlocal kernel has been used to fractionalize the blood alcohol model. The logical solutions of the absorptions of liquor in stomach S ( t ) and the absorptions of liquor in the blood B ( t ) have been explored by using the Laplace transform technique and are stated in the forms of the generalized G ‐functions G a, b, c (·) and the bivariate Mittage–Leffler functions. Further, we present a detailed analysis including numerical explanation and stability analysis.